The local human capital cost of oil exploitation - Lenin H. Balza; Camilo de los Rios Rueda; Raul Jimenez Mori; Osmel Manzano (Inter-American Development Bank (IDB), 2021)
This paper explores the impacts of oil exploitation on human capital accumulation at the local level in Colombia, a resource-rich developing country. We provide evidence based on detailed spatial and temporal data on oil exploitation and education, using the number of wells drilled as an intensity treatment at the school level. To find causal estimates we rely on an instrumental variable approach that exploits the exogeneity of international oil prices and a proxy of oil endowments at the local level. Our results indicate that oil has a negative impact on human capital since it reduces enrollment in higher education. Furthermore, it generates a delay in the decision to enroll in higher education and leads students to prefer technical areas of study and programs in social science, business, and law. However, we do not find any effects on quality or tertiary education completion. Our results are robust to a number of relevant specification changes and we stress the role of local markets and spillovers as the main transmission channel. In particular, we find that higher oil production causes an increase in formal wages but that there is no premium to tertiary education enrollment.
Keywords: I23; Q32; Q35; 330; Natural Resource Exploitation; Human Capital; Colombia